If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 6)(3x + 10) = 0 Reorder the terms: (6 + 2x)(3x + 10) = 0 Reorder the terms: (6 + 2x)(10 + 3x) = 0 Multiply (6 + 2x) * (10 + 3x) (6(10 + 3x) + 2x * (10 + 3x)) = 0 ((10 * 6 + 3x * 6) + 2x * (10 + 3x)) = 0 ((60 + 18x) + 2x * (10 + 3x)) = 0 (60 + 18x + (10 * 2x + 3x * 2x)) = 0 (60 + 18x + (20x + 6x2)) = 0 Combine like terms: 18x + 20x = 38x (60 + 38x + 6x2) = 0 Solving 60 + 38x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(30 + 19x + 3x2) = 0 Factor a trinomial. 2((10 + 3x)(3 + x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(10 + 3x)' equal to zero and attempt to solve: Simplifying 10 + 3x = 0 Solving 10 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = 0 + -10 3x = 0 + -10 Combine like terms: 0 + -10 = -10 3x = -10 Divide each side by '3'. x = -3.333333333 Simplifying x = -3.333333333Subproblem 2
Set the factor '(3 + x)' equal to zero and attempt to solve: Simplifying 3 + x = 0 Solving 3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + x = 0 + -3 x = 0 + -3 Combine like terms: 0 + -3 = -3 x = -3 Simplifying x = -3Solution
x = {-3.333333333, -3}
| -2x-8=4x+16 | | 3z^2-7z+4=0 | | 5(-1)-2= | | 176-6x=39x-21 | | 0.45(5-0.4n)=-3.2 | | 5x-2=-2x-9 | | 3-18+8x=67 | | 2(-3+4y)=-6 | | 6m/5=24 | | -8*x+3=251 | | 15y^2+46y+16=0 | | 17p-3=48 | | 4x+2=2x+24 | | x^4+3x^2-54=0 | | 4w^2=-28w | | =3ln(8) | | 7t-8=4t-2 | | 3x-8=10-3x | | 5n(2n+8)=0 | | -5x+4=-40+6x | | (2x^3)x(8x^8)= | | 9x^2+2x=10x | | 6s-10=-3x+8 | | -15=-30 | | 7(6-7x)=-56 | | ax^2+8x-3=4 | | -7(10+4x)=-238 | | 5x^2-15=45 | | -x+2=-61+6x | | (2-5i)(p+q)i=29 | | 6x-64=4x-8 | | -3*f-14=1 |